Využití kogenerace a trigenerace pro energetické zásobování odlehlých objektů - Fojtík, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
Diplomová práce se zabývá využitím kogenerace a trigenerace pro energetické zásobování odlehlých objektů. První část obsahuje popis technologií a způsoby realizace. Je v ní také popsán absorpční oběh. Druhá část je zaměřena na řešení energetické soběstačnosti budovy s definovanými energetickými nároky včetně ekonomického vyhodnocení.

This diploma work deals with the topic application of cogeneration and trigeneration for outlying buildings supplying. The first part this work containes description of technology and methods of realization. In this part there is also described absorption circulation. The second part this work targets concepts energy independedce the building, that has concrete energy consumption, including economic analysis.
Application of cogeneration and trigeneration for outlying buildings supplying
Keywords: kogenerace trigenerace absorpce; cogeneration trigeneration absorption